Favoritism and flooding: Political alignment and allocation of irrigation water. (February 2019) - Beg, Sabrin
Highlights: Exogenous variation from close elections and rainfall shocks is used. Ruling party representatives allocate irrigation water toward aligned regions. Incentives to favor aligned regions affects flood incidence. Political alignment mitigates the negative affect of rainfall shocks on agricultural yield. Abstract: Using a context where agriculture relies on uncertain rainfall and irrigation, I demonstrate that ruling party representatives counteract rainfall variability to benefit politically aligned regions through favorable irrigation water supply. First, I demonstrate average river water supply and flood incidence respond to the identity of the ruling party. I then exploit close elections to get random variation in a region's alignment with the political party in power, exogenous rainfall shocks to measure drought/flood risk and river water flow rate as a measure of water supply at any location. I find that water supply is in favor of upstream districts and against downstream districts when upstream districts are aligned with the ruling party and vice versa when down-stream district are more aligned; consequently, floods (or droughts) are more likely to occur in downstream regions when the ruling party has lower incentives to favor them. Agricultural productivity in politically aligned areas responds positively to the preferential delivery of resources. I argue that the ruling party's influence over autonomous agencies that monitor dam usage and water allotment allows its members to reward their constituents. The paper offers novel insights into how political factors determine resource allocation and into the resulting environmental and economic impact.